2010
DOI: 10.1039/c0dt00766h
|View full text |Cite
|
Sign up to set email alerts
|

CH-Anion versus anion-π interactions in the crystal and in solution of pentafluorobenzyl phosphonium salts

Abstract: A series of phosphonium salts with pentafluorobenzyl substituents have been synthesized and were investigated in the crystal as well as in solution. The solid state structures of 1a, 1b and 2d reveal the presence of anion-π as well as CH-anion interactions. The two attractive, yet competitive forces seem to act in concert and a directing effect of the CH interaction on the relative position between anion and π-system is observed. The search for anion-π interactions in solution failed. Only CH-anion interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Our earlier studies showed the appropriateness of (pentafluorobenzyl)phosphonium salts as target molecules for the study of anion‐π interactions in the solid state 15. In addition to previously described structures of pentafluorobenzyl phoshonium halides, we herein report the corresponding tetrafluoroborate ( 3c ), hexafluorophosphate ( 3d ), and hydrosulfate ( 3e ) structures.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Our earlier studies showed the appropriateness of (pentafluorobenzyl)phosphonium salts as target molecules for the study of anion‐π interactions in the solid state 15. In addition to previously described structures of pentafluorobenzyl phoshonium halides, we herein report the corresponding tetrafluoroborate ( 3c ), hexafluorophosphate ( 3d ), and hydrosulfate ( 3e ) structures.…”
Section: Resultsmentioning
confidence: 68%
“…Triphenyl(pentafluorobenzyl)phosphonium Bromide 3a: Synthesized according to a previously described procedure 15…”
Section: Methodsmentioning
confidence: 99%
“…[12c] Triphenyl(pentafluorobenzyl)phosphonium bromide was synthesized by treating triphenylphosphine with pentafluorobenzyl bromide according to al iterature method. [20] 2-Phenylacetonitrile and 2-perfluorophenylacetonitrile were obtained from commercial sources and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…First attempts to find some relevance of anion -p interactions in solution by studying pentafluorobenzyl phosphonium salts show no evidence for this intermolecular force in chloroform (13).…”
Section: Introductionmentioning
confidence: 99%